Pengaruh Persepsi Nilai dan Kesadaran Kesehatan Terhadap Minat Beli Makanan Organik Pada Kaum Millenial - Taviprawati, Ervina; Prabandari, Wijayanti Dewi; Tarigan, Emenina; Enggriani, Mimi (Jurnal Ilmiah Pariwisata, 2023)
This study aims to determine the effect of value perceptions and health awareness on the intention to buy organic food among millennials. This type of research is descriptive quantitative with multiple analytical methods. The population in this study are all millennials aged 19 to 38 years. The sample in this study was 100 respondents using accidental sampling. The location in this study is millennials in South Jakarta. In this study, the value perception variable has a significant effect on the intention to buy organic food among millennials, because there is a positive perception as a result of consuming organic food, the body becomes healthier and avoids disease, so many millennials are interested in buying organic food. Then the health awareness variable has a significant effect on the intention to buy organic food among millennials, because millennials are aware of the benefits of organic food not using chemicals, it is assumed that there are quite a lot of them for health because organic food contains antioxidants that protect cells from damage caused by free radicals, so many Millennials are interested in buying organic food. Keywords: Value Perceptions, Health Awareness, Interest To Buy